Knowledge, Attitude, and Practices of Hepatitis B Among Emergency Healthcare Workers in Lahore - Gohar, Awais; Naeem, Muhammad; Amjad, Muhammad; Shah, Rabia Iftikhar; Khan, Iqra Hamid (Biological and Clinical Sciences Research Journal, 2025)
Background: Hepatitis B (HB) remains a significant public health concern globally, particularly among healthcare workers who are at high risk due to exposure to infected bodily fluids. Objective: This study aimed to evaluate the knowledge, attitudes, and practices (KAP) regarding Hepatitis B among Rescue 1122 workers in Lahore, Pakistan. Methodology: This cross-sectional analytical study was conducted over nine months at the Emergency Services Academy-Rescue 1122 in Lahore, involving 358 EMTs selected via simple random sampling. A self-designed questionnaire, with a Cronbach’s alpha of 0.76, assessed knowledge, attitude, and practices (KAP) related to Hepatitis B. Descriptive statistics and Chi-square tests were used for data analysis, with significance set at P ≤ 0.05. Results: 358 questionnaires were distributed with a response rate of 100%, and they seem to have an association with education, experience with Rescue 1122, age, residence, and various other sociodemographic factors. The determinants for inadequate knowledge included gender and residency. At the same time, negative attitude can also be determined on the basis of education and similarly, health awareness education was only determinant for poor practices. Conclusion: results from this study show that knowledge and practices were adequate and good, respectively. Therefore, it reaffirms that adequate knowledge yields good practices and subsequently careful coverage of the Hepatitis B vaccine.